Investigating the Mutations in atpE and Rv0678 Genes in Mycobacterium Tuberculosis Clinical Isolates - Nahid Madadi-Goli1, 2, 3; Kamal Ahmadi1, 2 , 3; Sharareh Khanipour1, 2; Shahin Pourazar Dizaji1, 2; Mahshid Nasehi4, 5; Seyed Davar Siadat1, 2; Farzam Vaziri1, 2; Abolfazl Fateh1, 2* (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Tuberculosis (TB) caused by the bacterium Mycobacterium tuberculosis remains a critical global public health concern due to the high morbidity and mortality rates. Mutation in atpE and Rv0678 genes contributes to drug resistance in M. tuberculosis. This study investigates the antibiotic resistance patterns and mutations in atpE and Rv0678 genes in 22 M. tuberculosis clinical isolates. Methods: Drug susceptibility testing (DST) for rifampin, isoniazid, streptomycin, capreomycin, ofloxacin, kanamycin, and ethambutol was conducted using the proportional method. This was followed by determining the minimum inhibitory concentration (MIC) for bedaquiline (BDQ) via the microplate Alamar blue assay (MABA). Genomic regions encompassing atpE and Rv0678 genes were amplified and sequenced for mutation analysis. Data analysis was performed using SPSS software to interpret mutation patterns concerning drug susceptibility profiles. Results: Of 22 isolates, 5 (27.8%) were extensively drug-resistant tuberculosis (XDR-TB), and 13 (72.2%) were multi-drug resistant tuberculosis (MDR-TB). Resistance rates to kanamycin, ofloxacin, capreomycin, and streptomycin were 40.6%, 46.3%, 85%, and 74.6%, respectively. Additionally, phenotypic resistance to bedaquiline was observed in 12 (54.5%) isolates. Sequencing revealed no resistanceconferring mutations in the atpE or Rv0678 genes among the isolates. Conclusion: Our findings showed substantial resistance to first- and secondline drugs in M. tuberculosis clinical isolates. This highlights the necessity for ongoing, comprehensive studies to elucidate the evolving drug resistance patterns and understand the underlying mechanisms in clinical isolates.